The Effect of Whole Body Electromyostimulation Exercises on Improving Static Balance and Self-Efficacy in the Elderly - Ahmadpour, Maedeh; Rezaei, Meysam (Health Nexus, 2023)
The primary aim of this research was to investigate the effect of electrical muscle stimulation (EMS) on the enhancement of static balance and self-efficacy in elderly individuals. This quasi-experimental study employed a pre-test and post-test design, encompassing two groups: an experimental group and a control group. The study involved elderly women aged between 65 and 70 years from Mashhad. Twenty participants from this age group were voluntarily and selectively recruited in accordance with the objectives of the study. They were then randomly divided into two groups: one receiving EMS training and the other serving as a control group. Data collection involved administering the Elderly Self-Efficacy Questionnaire and conducting static balance tests, including the use of a Biodex device and the Sharpened Romberg test, at both the pre-test and post-test phases. The EMS training lasted for 8 weeks, with two 20-minute sessions per week, and was divided into three phases: adaptation (2 weeks), initial exercises (2 weeks), and main exercises (4 weeks). The control group did not receive any intervention during this period. Post-test evaluations were conducted for both groups, similar to the pre-test. The Multivariate Analysis of Covariance (MANCOVA) was used to analyze changes both within and between groups, employing a significance threshold of less than five percent, with the analysis conducted using SPSS software, version 24. The findings indicated that EMS exercises significantly improved static balance in the elderly (p < 0.05). However, these exercises did not demonstrate a significant effect on the elderly’s self-efficacy (p < 0.05). Given these results, coaches and caregivers are encouraged to consider electrical muscle stimulation as a viable, safe method to augment balance and independent mobility in elderly women.